Can the supplementation of vitamin D, sun exposure, and isolation during the COVID-19 pandemic affect the seasonal concentration of 25(OH)D and selected blood parameters among young soccer players in a one-year training season? - Joanna Jastrzębska; Maria Skalska; Łukasz Radzimiński; Guillermo F. López Sánchez; Lee Hill; Katja Weiss; Beat Knechtle (Taylor & Francis Group, 2023)
Objective This study examined the effect of vitamin D supplementation, sunlight radiationradiation, and home isolation during the COVID-19 pandemic on the seasonal changes in 25(OH)D concentration and selected biomarkers in young soccer players along a one-year training cycle. Method Forty elite young soccer players (age: 17.2 ± 1.16 years, body mass: 70.2 ± 5.84, and body height: 179.1 ± 4.26 cm) participated in the research. Only 24 players completed the measurements during all four time- points (T1-: September 2019, T2-: December 2019, T3-: May 2020, and T4-: August 2020) and were divided into two subgroups: supplemented group (GS) and placebo group (GP). Players from GS received 5,000 IU of vitamin D for 8 weeks (January-MarchJanuary-March 2020). Several biomarkers such as 25(OH)D, white blood cells (WBC), red blood cells (RBC), hemoglobin (HGB), muscle damage markersmarkers, and lipid profile were measured. Results AnalysisThe analysis of the total group demonstrated significant seasonal changes in 25(OH)D, HGB, asparagine aminotransferaseaminotransferase, and creatine kinase along the one1-year training cycle. The level of 25(OH)D concentrationinconcentration in T4 was significantly (p < 0.001, pη [ = 0.82) higher in both subgroups in comparison to T2 and T3. Moreover, the significant (p = 0.023) but poor (r = −0.23) correlation between 25(OH)D and WBC was calculated. Conclusion Current research confirmed the significant seasonal changes in 25(OH)D concentration during four seasons. 8-weekEight-week vitamin D supplementation had no extended effect on the level of 25(OH)D concentration.